DESIGN OF A HIGH EFFICIENCY POWER AMPLIFIER FOR WIRELESS AND RADAR APPLICATIONS - Mahouti, Peyman; Belen, Mehmet Ali; Partal, Hakan Pasa; Demirel, Salih; Gunes, Filiz (YILDIZ TECHNICAL UNIV, 2015)
This article reports a 46% efficient Class-A power amplifier (PA) designed for wireless transceiver communication systems. The compensation elements with a series capacitor and a shunt inductor are used to compensate for the internal parasitic components of the packaged transistor. The peak PA efficiency of 46% with a power gain of 18 dBm is achieved at an input power of 0dBm for a continuous wave designed for 1850-1950 MHz. To improve output power and efficiency by suppressing harmonic powers, an output matching circuit using the transmission lines is used. The power amplifier exhibits a 0Bm, 18-dB power gain while using a low quiescent current of 56 mA. The simulation results of the designed PA are found to be useful for many commercial wireless and radar applications, since it is compact in size, low loss, and cost with good performance. The PA can be scaled to the commercial frequencies up to 2.5GHz, offering advantages for most ISM and cellular band applications. This work demonstrates the feasibility of using class-A PAs for short-range, low-power applications.
Keywords: Power amplifiers; high efficiency power amplifiers; wireless transceivers; Engineering